The Development of an Earthquake Mind Mapping - Sri Adelila Sari; Nurul Husna (Journal of Education and Learning (EduLearn), 2016)
The students were difficult to understand about earthquake caused the teaching methods used by teachers were still using the classic method. The teachers only used a textbook to teach the students without any other supporting equipments. Learning process by using the discourse method makes students thinking monotonically, so that only concentrated on the students' understanding of the matter presented by the teacher. Therefore, this study was aimed to develop an earthquake mind mapping to help students in the process of remembering and recording the material being taught by the teacher. The type of this study was Research and Development (R and D). Data were analyzed using descriptive statistics. The samples in this study were class of I-3Madrasah Tsanawiyah (MTs) Darul Ulum Banda Aceh totaling 30 students. The results showed that mind mapping was developed by 5 stages in ADDIE models: analysis (analyzing the problem and find a solution), design (determine the learning strategies), development (producing an earthquake mind mapping to be used in the learning process), implementation (implementing learning activities using the media) and evaluation (evaluating the learning activities). When students instructed to create their mind mapping, it was found that the products of mind mapping categorized in skilled and quite skilled were amounted to 73.33 and 26.66% respectively. As recommendation an earthquake mind mapping could be applied and useful as an effective learning.